Fluorinated chlorin chromophores for red-light-driven CO2 reduction - Shuang Yang; Huiqing Yuan; Kai Guo; Zuting Wei; Mei Ming; Jinzhi Yi; Long Jiang; Zhiji Han (Nature Communications, 2024)
Abstract The utilization of low-energy photons in light-driven reactions is an effective strategy for improving the efficiency of solar energy conversion. In nature, photosynthetic organisms use chlorophylls to harvest the red portion of sunlight, which ultimately drives the reduction of CO2. However, a molecular system that mimics such function is extremely rare in non-noble-metal catalysis. Here we report a series of synthetic fluorinated chlorins as biomimetic chromophores for CO2 reduction, which catalytically produces CO under both 630 nm and 730 nm light irradiation, with turnover numbers of 1790 and 510, respectively. Under appropriate conditions, the system lasts over 240 h and stays active under 1% concentration of CO2. Mechanistic studies reveal that chlorin and chlorinphlorin are two key intermediates in red-light-driven CO2 reduction, while corresponding porphyrin and bacteriochlorin are much less active forms of chromophores.